Mechanistic Insights into Vegetable Color Stability: Discoloration Pathways and Emerging Protective Strategies - Jianing Zhang; Junjun Zhang; Lidan Zhang; Yuhong Xue; Ke Zhang (Foods, 2025)
During processing and storage, vegetables often experience undesirable color changes, including fading, lightening, or yellowing and softening, due to browning (enzymatic and non-enzymatic) and chlorophyll degradation. These changes diminish commercial and nutritional value. Therefore, it is necessary to maintain vegetable color and improve the quality of vegetable-based dishes. To address these issues, it is a scientific and practical necessity to summarize and discuss existing strategies and innovative techniques. This review first highlights the mechanisms of vegetable browning. This review then provides a comprehensive overview of recent advances in methods for color preservation, focusing on underlying mechanisms and techniques for inhibiting color changes from physical, chemical, and biological perspectives. A review of innovative technologies suggests that effective color preservation in vegetables is achieved by inhibiting the conditions that lead to three unfavorable color change reactions: enzymatic browning, non-enzymatic browning, and chlorophyll degradation. Current research frequently employs combined approaches that integrate two or more techniques to mitigate these adverse color changes. Moreover, most of these methods could simultaneously inhibit the three reaction processes. Future research directions are proposed for in-depth investigations into the molecular mechanisms of color changes in vegetables and the impact of treatments on the nutritional value.